Expected impact of immunomodulatory agents during pregnancy: A newborn's perspective. Issue 2 (7th February 2023) - Luo, Yiyi; Acevedo, Daniel; Baños, Núria; Pluma, Andrea; Castellanos‐Moreira, Raúl; Moreno, Estefania; Rodríguez‐García, Sebastian; Deyà‐Martínez, Angela; García‐García, Ana; Quesada‐Masachs, Estefania; Torres, Mireia; Casellas, Manel; et al.
Abstract: The neonatal immune ontogeny begins during pregnancy to ensure that the neonate is well‐suited for perinatal life. It prioritizes Th2/M2 and regulatory responses over Th/M1 activity to avoid excessive inflammatory responses and to ensure immune tolerance and homeostasis. Newborns also present increased Th17/Th22 responses providing effective anti‐fungal immunity and mucosal protection. Intrauterine exposure to immune modulatory drugs with the placental transfer may influence the natural course of the fetal immune development. The vertical transfer of both biological therapy and small molecules begins during the first trimester through neonatal Fc receptor or placental diffusion, respectively, reaching its maximum transfer potential during the third trimester of pregnancy. Most of the biological therapy have a prolonged half‐life in newborn's blood, being detectable in infants up to 12 months after birth (usually 6–9 months). The use of immunomodulators during pregnancy is gaining global interest. Current evidence mainly reports birth‐related outcomes without exhaustive analysis of the on‐target side effect on the perinatal immune system ontogeny, the infection risk, or the immune dysregulation. The present review will focus on: (1) the main characteristics of the perinatal immune system to understand its specific features and vulnerabilities to immune modulation; (2) the mechanisms of placental transfer of immunomodulators; and (3) the immune changes reported to date in newborns exposed to immunomodulators with emphasis on the current concerns and gaps in knowledge.